Regulation of House and Shop or Shophouse Development in Jambi City Based on Urban Spatial Planning Concept - Kurniadi, Wahyu (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
In the context of state administrative law, the government or state administration is responsible for granting building permits, particularly for houses with shops or commercial buildings (ruko). Legality is the main principle, and permits are considered crucial instruments in controlling spatial utilization to maintain urban planning. Key factors, such as land capacity and building function, are considerations in issuing permits, which must align with the local Spatial Planning Plan (RTRW). Legislation, especially Law Number 26 of 2007 concerning Spatial Planning, and Regional Regulations (Perda) of Kota Jambi, provide a legal basis for commercial building permits. However, the lack of specific provisions regarding houses with shops in the Building Regulation of Kota Jambi is a regulatory weakness. Uncontrolled commercial building development and insufficient guidance lead to numerous vacant or non-compliant commercial buildings. Main challenges involve a lack of location clarification, insufficient guidance, weak supervision, limited community participation, and a lack of understanding of administrative and technical building requirements. Solutions include developing additional guidelines, providing guidance for business owners, enhancing supervision, increasing community participation, and offering technical consultation services. Clearer clarification and practical solutions are expected to ensure that commercial building development contributes positively to urban planning and fulfills public interests and environmental sustainability.